Batasan Kewenangan Penyidik Anak Terkait Pelaksanaan Diversi dalam Proses Penyelesaian Perkara Tindak Pidana Anak - Megah Novita Endriyanti; Nurini Aprilianda; Abdul Madjid (Jurnal Cakrawala Hukum, 2018)
This paper aims to analyze the limits of the authority of the child investigator related to the implementation of diversion in the process of resolving cases of child crimes. To answer the purpose of this paper, normative legal research is used, using the legal approach and case. The results of the study indicate that child investigators in solving cases of child crimes can apply discretion related to the implementation of diversion. The authority limit for discretion of child investigators, namely the reason for implementing diversion that does not fulfill the implementation requirements in the SPPA Law, must be logical and reasonable, not for serious crimes such as criminal acts against the body and life, and not repetitive crimes. In the case of theft with weights, the results of which have been determined by the Chairperson of the Pasuruan City District Court, discretion is taken by the police with various considerations. One of them is because the perpetrators and the victims agreed that the case would be settled in a family manner because the perpetrator still had a brotherly relationship with the victim. Therefore, with several agreements the victims decided to settle the case outside the court process, namely diversion.How to cite item: Endriyanti, M., Aprilianda, N., Madjid, A. (2018). Batasan Kewenangan Penyidik Anak Terkait Pelaksanaan Diversi dalam Proses Penyelesaian Perkara Tindak Pidana Anak. (2), 204-213. doi:https://doi.org/10.26905/idjch.v9i2.2259